MiRNA‐34c‐5p targets Fra‐1 to inhibit pulmonary fibrosis induced by silica through p53 and PTEN/PI3K/Akt signaling pathway. Issue 8 (2nd May 2022) - Pang, Xinru; Shi, Haojun; Chen, Xiaoshu; Li, Chao; Shi, Bin; Yeo, Abrey J.; Lavin, Martin F.; Jia, Qiang; Shao, Hua; Zhang, Juan; Yu, Gongchang
Abstract: Silica dust particles are representative of air pollution and long‐term inhalation of silicon‐containing dust through the respiratory tract can cause pulmonary fibrosis. Epithelial‐mesenchymal transformation (EMT) plays an important role in the development of fibrosis. This process can relax cell–cell adhesion complexes and enhance cell migration and invasion properties of these cells. Dysregulation of microRNA‐34c (miR‐34c) is highly correlated with organ fibrosis including pulmonary fibrosis. In this study, we found that miR‐34c‐5p could alleviate the occurrence and development of silica‐mediated EMT. Fos‐related antigen 1 was identified as a functional target of miR‐34c‐5p by bioinformatics analysis and the dual luciferase gene reporting assay. Importantly, chemically induced up‐regulation of hsa‐miR‐34c‐5p correlated inversely with the expression of Fra‐1 and further exploration found that the miR‐34c‐5p/Fra‐1 axis inhibits the activation of the phosphatase and tensin homolog deleted on chromosome 10/phosphatidylinositol‐4, 5‐bisphosphate3‐kinase/protein kinase B (PTEN/PI3K/AKT) signaling pathway. In addition, through interaction with PTEN/p53 it inhibits the proliferation and migration of human bronchial epithelial cells stimulated by silica, and promotes cell apoptosis, thereby preventing EMT. This finding provides a promising biomarker for the diagnosis and prognosis of pulmonary fibrosis. Furthermore, overexpression of miR‐34c‐5p represents a potential therapeutic approach.